Unlocking brand equity through brand image, service quality, and customer value - Rina Dewi; Tanti Handriana (BISMA (Bisnis dan Manajemen), 2021)
Building brand equity in customers is essential to create long-term relationships with customers. With high brand equity, the company maintains loyal customers because consumers believe in its quality or service. This study aims to determine how the brand image, satisfaction with service quality, and customer value affect brand loyalty and equity. This research is a quantitative study which collected 215 samples with purposive sampling method. The analysis technique uses Structural Equation Modeling. The results show a brand image, service quality, and customer value are positively affect brand loyalty. The loyal customer attitude influence long-term brand equity. This finding offers a theoretical and practical contribution to developing a marketing management strategy about unlocking brand equity through a strong brand image, service quality, and customer value in the banking sector.